Notes on protected and threatened plants in Castilla y León (North-West Spain) - del Egido, Fermín; Bariego, Patricio; Rodríguez, Alberto; Santos Vicente, María (Mediterranean Botany, 2020)
We provide new records and notes on 25 protected and/or threatened vascular plant species in Castilla y León. Some of them illustrate not only new findings but also an interesting expansion of their geographic range. Eight taxa are reported for the first time in some provinces, while eleven of them were two or three times previously reported.